Prevalence Level and Predictors of Face to Face and Cyberbullying in Selected Service Sectors of Pakistan. - Iftikhar, Mehwish; See Beh, Loo (International Journal of Engineering and Technology, 2018)
There found a scarcity of academic research on understanding of both the traditional and cyberbullying jointly at workplace of organisations. As an emerging field of research area, detailed understanding about the predictors of cyberbullying has yet not been fully established. Drawing on the sample of 285 officials working in 4 service sectors [banking, telecom, hoteling and education] of Pakistan, this research endeavoured to investigate about prevalence rate, extent and frequency of both the traditional and cyberbullying and predictors responsible for causing bullying among workers of service sectors of Pakistan. Using NAQ-21 and NAQ-R on the basis of the laymanâ€™s cut-off criteria for measuring bullying and cyberbullying prevalence, results highlighted that 36%, 55%, 50% and 59% of the respondents were categorised as bullied traditionally and 18%, 30%, 27% and 49%Â were cyberbullied in education, banking, telecom and hoteling service sectors respectively, and this is unfortunately a very high ratio. Overall bullied [traditionally] percentage was 50 and cyberbullied was 31. Smart PLS-SEM based analysis verified that, multiple dimensions of organisational climate were found to be the predictors of workplace bullying, while technology [social networking and ICTâ€™s] is significantly related to the prevalence of cyberbullying at workplace of service sector organisations. This research provides new insights about new type of bullying i-e cyberbullying and its predictors/causes. Prevalence percentages of workplace traditional and cyberbullying have also been determined that shows bullying spread in service sectors at an alarming rate, which needs to be controlled.Â